Molecular thermodynamics for cell biology as taught with boxes - Mayorga, Luis Segundo (2012)
Thermodynamic principles are basic to an understanding of the complex fluxes of energy and information required to keep cells alive. These microscopic machines are nonequilibrium systems at the micron scale that are maintained in pseudo-steady-state conditions by very sophisticated processes. Therefore, several nonstandard concepts need to be taught to rationalize why these very ordered systems proliferate actively all over our planet in seeming contradiction to the second law of thermodynamics. We propose a model consisting of boxes with different shapes that contain small balls that are in constant motion due to a stream of air blowing from below. This is a simple macroscopic system that can be easily visualized by students and that can be understood as mimicking the behavior of a set of molecules exchanging energy.With such boxes, the basic concepts of entropy, enthalpy, and free energy can be taught while reinforcing a molecular understanding of the concepts and stressing the stochastic nature of the thermodynamic laws. In addition, time-related concepts, such as reaction rates and activation energy, can be readily visualized. Moreover, the boxes provide an intuitive way to introduce the role in cellular organization of "information" and Maxwell's demons operating under nonequilibrium conditions.